Upaya Peningkatan Mutu Pendidikan Melalui Sistem Informasi Manajemen - Dasep Supriatna; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Journal on Education, 2024)
This examination plans to portray endeavors to work on the nature of schooling through administration data frameworks. This examination utilizes a subjective methodology utilizing perception, meetings and documentation as information assortment procedures. The examination results show that the execution of the Training The board Data Framework (SIMDIK) comprises of instructing and schooling staff administrations by engaging the SIMPATIKA application (Service of Religion Data Framework for Instructors and Instruction Faculty), e-learning applications, BNI eduPATROL applications, finger impression applications the two educators and understudies and online applications in tolerating new understudies. In executing the utilization of the Training The executives Data Framework (SIMDIK) there are driving elements and restraining factors. The driving variables incorporate the presence of the SIMPATIKA data framework which gathers information on the two understudies and teachers, instruction staff (PTK). Aside from that, there is participation from different gatherings both concerning foundation and HR in supporting as a madrasa that executes a digitalization framework. With respect to the snags that cause not exactly ideal execution of SIM , including more seasoned educators who experience trouble in following or doing SIM execution, aside from that, blunders frequently happen in SIM innovation, and in learning understudies experience trouble in fulfilling time constraints. the time indicated for reporting inclusion of school exercises.